Pengaruh Tingkat Kepuasan Pengguna Lulusan (Stakeholder) Terhadap Kualitas Lulusan Pada Universitas Teknologi Sumbawa - Nora Dery Sofya; Mohammad Taufan Asri Zaen; Yuliadi Yuliadi; Sansul Yasmi (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Sumbawa University of Technology (UTS) is an educational institution that produces outputs that match work needs. The curriculum is to develop a number of study programs at UTS, adapted to the developments and demands of today's world of work. This research was conducted to determine the level of satisfaction of Stakeholders on the quality of graduates. Research is using a descriptive method with a quantitative approach. Analysis data method uses the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). Respondents in this study were graduate users (Stakeholders) with a total of 100 respondents. The results of this study, that the quality of graduates from UTS is very good, even though they work not in their field of expertise (non-academic). Even though the quality of the graduates is in the category very good, there are several items/attributes that need to considere. In meeting the satisfaction of Stakeholders, namely Point number 9 regarding the ability of graduates to write activity reports. , such as research and projects. The second point, number 14 is the ability of graduates to use technology related to their field of science. Item number 15 is the graduate's ability to use computers.